ANALISIS INOVASI ROTI 7 LAPIS PEMADAM KEBAKARAN DI SURABAYA DALAM PERSPEKTIF NEW PUBLIC GOVERNANCE - Anita Nenci Lia (Universitas Bina Taruna Gorontalo, 2023)
This study aims to determine the effect of the innovative concept of Roti 7 Lapis Response Time 7 Minutes in increasing efficiency and effectiveness in fire fighting services at the Surabaya City Fire and Rescue Service or DPKP in the perspective of New Public Governance. The subject of this research is the Surabaya City Fire and Rescue Department or DPKP. For this reason, this research uses qualitative methods using case studies with data collection techniques through observation and documentation. Discusses aspects of formulation, implementation, evaluation, and bureaucratic reform using public policy concept theory. The results of the study show that the 7-minute Response Time carried out by DPKP Surabaya is implemented through the appropriate stages. This 7-minute Response Time policy can be felt by all groups in community because the target is all residents of the city of Surabaya without exception and is also in line with the goals of Sustainable Development Goals (SDGs) and in accordance with the vision and mission of the Surabaya City Fire and Rescue Department.